The cutter - Suárez, Virgil, 1962- (Pioneers of modern U.S. Hispanic literature., 2017)
When his family tries to immigrate to the United States, Julian Campos is turned away at the border, while his parents are allowed to go on. To get his papers, Julian must "volunteer" to return to the sugarcane fields as a cutter to help harvest the tons of cane in Cuba. Forced to do backbreaking labor behind barbed wire fences, Julian struggles along until he is told he will be returned to the army. Seeing no other way out, Julian and some of his fellow cutters plan a daring escape to the United States.